Pengiklanan srategik: jenama global di Malaysia - Mohd Helmi Abd. Rahim,; Maizatul Haizan Mahbob,; Wan Idros Wan Sulaiman, (2009)
Globalization has created interdependence of cultures and countries from around the world. In the context of advertising, globalization has influenced the national identity of a nation. Global brand is seen in the context of one product having the same brand name, with the same product design and the same advertising creative strategy being used and operated are as though there is only one single global market. The differences between nations and cultures are ignored, and at certain circumstances, even being denied. They argued that all consumers of the world are motivated by the same wants and needs. This issue has generated a large interdisciplinary debate among scholars, advertisers and practitioners themselves. To address this issue, 200 television commercials are content analyzed in an attempt to examine how commercials in Malaysia tackled the issue, especially in balancing Western images and influences against the portraying of local identities. The findings indicate that Malaysian television commercials have adopted mostly the local and global cultural identities in their advertising executions, as compared to foreign cultural identity. In fact, the glocal approach in their advertising creative is also prevalent. On the other hand, another form of standardization, namely Asian standardization, has been found in the research findings as another strategic advertising form used by advertisers.